Warehouse Operations Measurement in Hypermarket Retailers. A Review of Literature - Vatumalae, Vellian; Rajagopal, Premkumar; Kaliani Sundram, Veera Pandiyan (International Journal of Supply Chain Management, 2020)
This paper aims to explore the warehouse operations measurement with the deployment of the Warehouse Management System of Hypermarket retailers in Malaysia. The warehouse operations measurement is vital for the organisation that manages the total distribution network in hypermarket retailers. A qualitative research approach to be adopted in conducting an in-depth case study in top of the hypermarket retailers in Malaysia warehouse operations located in northern and central Malaysia, offering most of logistics services including transportation and serving a large number of retail customer outlets in Malaysia. The sustainability of the Hypermarket retailers solely depends on the performance of its supply chain process and a balance between responsive and warehouse operations performance with the deployment of the Warehouse Management System. The Hypermarket retailer’s warehouse operations are striving to gain a competitive edge, such as fast market penetration, product availability at the right price and at the right place, warehouse productivity and cost competency having alternatives. Presently, there are some general guidelines to measure warehouse operations with the deployment but not specifically towards to Hypermarket retailing industry. The lack of clear measurement and comparability concerns resulted in a study to be carried out in determining the warehouse operations measurement in Malaysia hypermarket retailers, Based on this study, new sustainable Hypermarket retail warehouse operations measurement conceptual framework is proposed to enhance the body of knowledge of warehouse operations measurement in Malaysia, especially in hypermarket retailers